Disparities in Insurance Coverage, Health Services Use, and Access Following Implementation of the Affordable Care Act: A Comparison of Disabled and Nondisabled Working-Age Adults - Jae Kennedy PhD; Elizabeth Geneva Wood MHPA; Lex Frieden MA, LLD (SAGE Publishing, 2017)
The objective of this study was to assess trends in health insurance coverage, health service utilization, and health care access among working-age adults with and without disabilities before and after full implementation of the Affordable Care Act (ACA), and to identify current disability-based disparities following full implementation of the ACA. The ACA was expected to have a disproportionate impact on working-age adults with disabilities, because of their high health care usage as well as their previously limited insurance options. However, most published research on this population does not systematically look at effects before and after full implementation of the ACA. As the US Congress considers new health policy reforms, current and accurate data on this vulnerable population are essential. Weighted estimates, trend analyses and analytic models were conducted using the 1998-2016 National Health Interview Surveys (NHIS) and the 2014 Medical Expenditure Panel Survey. Compared with working-age adults without disabilities, those with disabilities are less likely to work, more likely to earn below the federal poverty level, and more likely to use public insurance. Average health costs for this population are 3 to 7 times higher, and access problems are far more common. Repeal of key features of the ACA, like Medicaid expansion and marketplace subsidies, would likely diminish health care access for working-age adults with disabilities.